KEBERLANJUTAN BIOTA SUNGAI SAIL KOTA PEKANBARU (STUDI KASUS DISTRIBUSI DAN KELIMPAHAN MAKROZOOBENTHOS) - Hasby, Muhammad; Thamrin, Thamrin; Sukendi, Sukendi (DINAMIKA PERTANIAN, 2017)
Study on the biota sustainability of Sail River in Pekanbaru city was carried out in Sail River on June 2014. The objective of this study was to identify the macrozoobenthos community structure and its relation to the physical and chemical parameters of Sail river. Water and macrozoobenthos samples were taken at each station with 3 replications at the 5 stations, namely a sampling point upstream, mid-stream and downstream Sail River. The samples were analyzed in the Laboratory of Aquatic Ecology, Fishery and Marine Science Faculty, Riau University. The results indicate the macrozoobenthos samples were consisted of 3 phylums, 4 classes and 10 specieses. The abudance of the organisms was 68-532 individu/m2 with the diversity index (H’) was 0,65-2,19, the domination index (C’) was 0,23-0,72 and the homogenity index was 0,65-0,94. The Ammonia (NH3) and Chemical Oxygen Demand (COD) of the water exceeded the maximum threshold suggested by the Goverment Decree No. 82 / 2001, the Management of Water Quality and Pollution. The results showed the positive correlation betwen macrozoobenthos with various physical and chemical characteristics of the water, and the sediment and texture of the bottom material.